IN SEARCH OF PROGRESS: GREEN REVOLUTION AND THE INFERIORIZATION OF PEASANT KNOWLEDGE - Marcatti, Amanda Aparecida; de Souza, Wanessa Alves Pereira (Revista Vozes dos Vales: Publicações Acadêmicas, 2023)
The Green Revolution is the technological and scientific paradigm that changed the logic of the agricultural question in Brazil and in the world. The search for capitalist progress through the process of industrialization of agriculture transformed the social relations of production in the countryside, but maintained and deepened socioeconomic inequalities as a contradiction of the process of modernization of the latifundia. In this article, we present the historical background that boosted the implementation of the Green Revolution in Brazil, as well as the social, economic and environmental consequences of this productive path for peasants. When examining the logic of capitalist progress in the countryside, we make explicit the artifice of inferiority of peasant knowledge and ways of life, with the advent of the Green Revolution. In short, we question the quest for capitalist progress and its universalization as a societal path. After half a century of the Green Revolution, food insecurity, the dependent economy and socio-environmental problems persist in the daily lives of rural and urban workers
Keywords: Progress; Green Revolution; Peasant Knowledge